Persepsi Mahasiswa terhadap Penikahan Dini dan Implikasinya Terhadap Layanan Bimbingan Konseling Islam - Fadil Maiseptian; Erna Dewita; Fitriani Fitriani (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2022)
The West Sumatra National Population and Family Planning Agency (BKKBN) explained that 6,083 couples married under the age of 20 between 2010-2015. Perceptions of students who do early marriage to protect themselves from acts that go beyond social boundaries. The purpose of this study was to describe the level of student perception about early marriage at the Faculty of Islamic Religion UM. West Sumatra. This study uses a quantitative method with a descriptive approach. The research sample was 129 students with a random sampling technique. The data collection technique used an instrument to measure students' perceptions of early marriage with a validity level of 0.02 and instrument reliability of 0.9. The data analysis technique used the percentage formula p=f/nx100. Student perceptions of early marriage at the Faculty of Islamic Religion UM. West Sumatra on the aspect of the cause of early marriage on average is in the quite positive category and from the aspect of the impact of early marriage on average, it is in the less positive category. Based on the results of this study, it is necessary to provide Islamic counseling services to improve student perceptions of early marriage.